The Effectiveness of Aramco F1 in Schools Program Based on STEAM Approach on Development Soft Skills of the Intermediate Stage Pupils - BuoEdrees, Raef Hassan (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to investigate the effectiveness of the Aramco Formula 1 program in schools (outside school hours) based on the integrated STEAM approach, and to study its effectiveness on developing soft skills for middle school students in Dhahran in the Kingdom of Saudi Arabia. The study used the Aramco Formula 1 program in schools to prepare students for international competition, which was designed by the King Abdulaziz Center for World Culture Ithra of Saudi Aramco on the topic (Engineering Design of Formula 1 Racing Cars in Schools), and a soft skills scale was prepared by the researcher, The educational program was also applied to one group consisting of (25) male and female students who were intentionally selected from six public, private and international schools affiliated to the Education Department in the Eastern Province. The results of the study revealed that there was a statistically significant difference between the mean scores of the research group in the two applications of the soft skills scale in favor of the post application, and that the Aramco Formula 1 program in schools is based on the integrated STEAM approach, very effective in developing soft skills (communication, cooperation, problem solving , negotiation, creativity and innovation), as the results of the study showed that there were no statistically significant differences in the skill scale for the dimensional application due to the variable of gender. The study recommended the interest of the Ministry of Education in implementing the Aramco Formula 1 program in schools at the level of education regions in the Kingdom, and interest in using the integrated STEAM approach in science and mathematics curricula in public education.
Keywords: ARAMCO; F1 in schools; STEAM educational approach; soft skills